Morphological Investigation of Foamed Aluminum Parts Produced by Melt Gas Injection. (22nd March 2009) - Surace, R.; De Filippis, L. A. C.; Niini, E.; Ludovico, A. D.; Orkas, J.
Abstract : Porous metal materials are a new class of materials with low densities, large specific surface, and novel physical and mechanical properties. Their applications are extremely varied: for light weight structural components, for filters and electrodes, and for shock or sound absorbing products. Recently, interesting foaming technology developments have proposed metallic foams as a valid commercial chance; foam manufacturing techniques include solid, liquid, or vapor state methods. The foams presented in this study are produced by Melt Gas Injection (MGI) process starting from melt aluminum. The aim of this investigation is to obtain complex foamed aluminum parts in order to make the MGI more flexible. This new method, called MGI-mould process, makes possible to produce 3D-shaped parts with complicated shape or configuration using some moulds obtained by traditional investment casting process.